Waiting for Recovery: The Canadian Labour Market in June 2020 - Stephen R. G. Jones; Fabian Lange; W. Craig Riddell; Casey Warman (Institute of Labor Economics (IZA), 2020)
The Canadian labour market is currently emerging from a holding pattern with unusually high numbers in temporary (or "recall") unemployment, those "employed but absent from work" for unspecified reasons, or not in the labour force while waiting to be recalled. Two encouraging signs are evident. New postings of vacancies have recovered from 50 percent to about 80 percent of their pre-crisis level. Also, data suggest that the increase in employment in May 2020 is due to some of those waiting to be recalled re-entering employment. These patterns suggest that the labour market might rebound quickly. Warning signs are that the shares of the unemployed without job attachment as well as those on recall engaged in job search are beginning to increase.
Keywords: J21; J22; J23; J63; 330; COVID-19; vacancies; unemployment; employment